A Case of Feline Papilliferous Mammary Adenocarcinoma with Widespread Metastases - Chen, Hsien-chuan (1968)
A papilliferous mammary adenocarcinoma with generalized metastasis, including multiple involvement of the brain, was found in a 14-year old female native born cat. No nervous signs except some behaviorial changes were noted.